Catalytic Processes for Water and Wastewater Treatment (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Catalytic oxidation or reduction processes are among the most efficient processes for water and wastewater treatment. These include photocatalysis, sulfate and hydroxyl-radical-based advanced oxidation processes.This Special Issue contains the contributions of different research groups and discusses the recent progress and advances in catalytic processes in water and wastewater treatment.